Simple, near, visual perception test for microsurgeon ‐Parallelism‐ - Tetsuya Hirata (Clinical and Experimental Dental Research, 2023)
Abstract Objectives It is well known that a good microsurgeon needs eight important factors: a high resolution view, an optimally magnified view, optimal brightness of the working field, optimal working space, fine surgical instruments and devices, fine motor skills, precise hand−eye coordination, and fine visual perceptions. Of these factors, the first five are highly depending on manufacturer development abilities. The remaining factors have a lots of possibilities that microsurgeons can improve by themselves. A microsurgeon needs to identify shape, size, angle, inclination, length, height, depth, spatial position, centering in the optical field, orthogonality, and parallelism in a second. Knowing one's tendency and acuity in perceptions, learning perceptions that one is not good at, and paying selective attention on one's difficult perceptions, will provide better surgical outcome. Aim of this series of research is designing visual targets measuring specific visual perceptions for microsurgeons, achieving mean values of each perceptions, and identifying the tendency on each perceptions. Material and Methods Two hundred and eighty volunteer dentists in Japan and France were tested and multiple comparisons were made among age, gender, visual acuity, three magnification levels, and inclination angles against a standard target. Results and Coclusion There is a tendency that identifying 1° misalignment in parallelism is difficult.